Stromal Derived Factor-1/CXCR4 Axis Involved in Bone Marrow Mesenchymal Stem Cells Recruitment to Injured Liver - Kuai Xiao Ling; Li Peng; Zhang Jian Feng; Cao Wei; Yuan Wei Yan; Shao Nan; Guan Cheng Qi; Wang Zhi Wei (Stem Cells International)
The molecular mechanism of bone marrow mesenchymal stromal stem cells (BMSCs) mobilization and migration to the liver was poorly understood. Stromal cell-derived factor-1 (SDF-1) participates in BMSCs homing and migration into injury organs. We try to investigate the role of SDF-1 signaling in BMSCs migration towards injured liver. The expression of CXCR4 in BMSCs at mRNA level and protein level was confirmed by RT-PCR, flow cytometry, and immunocytochemistry. The SDF-1 or liver lysates induced BMSCs migration was detected by transwell inserts. CXCR4 antagonist, AMD3100, and anti-CXCR4 antibody were used to inhibit the migration. The Sprague-Dawley rat liver injury model was established by intraperitoneal injection of thioacetamide. The concentration of SDF-1 increased as modeling time extended, which was determined by ELISA method. The Dir-labeled BMSCs were injected into the liver of the rats through portal vein. The cell migration in the liver was tracked by in vivo imaging system and the fluorescent intensity was measured. In vivo, BMSCs migrated into injured liver which was partially blocked by AMD3100 or anti-CXCR4 antibody. Taken together, the results demonstrated that the migration of BMSCs was regulated by SDF-1/CXCR4 signaling which involved in BMSCs recruitment to injured liver.